Photobiomodulation With Blue Laser Inhibits Bladder Cancer Progression - Xia, Yuqi; Yu, Weimin; Cheng, Fan; Rao, Ting; Ruan, Yuan; Yuan, Run; Ning, Jinzhuo; Zhou, Xiangjun; Lin, Fangyou; Zheng, Di (Frontiers in Oncology, 2021)
Blue lasers are becoming more widely used in the diagnosis and treatment of bladder cancer; however, their photobiomodulation effects on bladder cancer cells remains unclear. The purpose of the current study was to explore the photobiomodulation effect of blue laser irradiation on bladder cancer progression and the associated mechanisms. The human uroepithelial cell line SV-HUC-1 and human bladder cancer cell lines T24 and EJ were exposed to blue laser irradiation (450 nm) at various energy densities, and cell proliferation, migration, invasion, epithelial-mesenchymal transition (EMT), and the levels of the proteins associated with the MAPK pathway proteins were determined. A significant decrease in cell viability was observed in a density-dependent manner after blue laser irradiation at ˃ 4 J/cm2 in both bladder cancer cell lines. However, the blue laser did not reduce cell viability in SV-HUC-1 cells until the energy density exceeded 16 J/cm2. Meanwhile, Ki67 levels, reflecting cell proliferation and senescence, were also significantly decreased after blue laser irradiation at 4 J/cm2 and 8 J/cm2 in the absence of cell cycle arrest. Moreover, blue laser irradiation at 4 J/cm2 and 8 J/cm2 caused a reduction in cell migration and invasion and also reduced the expression levels of MMP-2, MMP-9, Snail, N-cadherin, phospho-MEK and phospho-ERK, and elevated the expression levels of E-cadherin. Meanwhile ERK activator(tBHQ) significantly reversed the irradiation-induced suppression of proliferation, migration and invasion in T24 and EJ cell lines. The present study showed that blue laser irradiation inhibited bladder cancer proliferation in a density-dependent manner and inhibited bladder cancer progression by suppressing migration, invasion, and the EMT process in T24 and EJ cell lines. This inhibition was possibly mediated via suppression of the MAPK/MEK/ERK pathway. Thus, the use of a low-energy blue laser in the diagnosis and treatment of bladder cancer is possibly safe and may have an anti-tumor effect.